2019
DOI: 10.1055/s-0039-1695006
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of the Electronic Health Record by Physicians

Abstract: Background Health information technology, especially the electronic health record (EHR) systems, improves health care quality and patient safety. Objectives This study's objectives are as follows: first, to explore the adoption of EHR systems among physicians in Saudi Arabia (with King Fahd Military Medical Complex as the location of the pilot study), and second, to identify the factors that influence these physicians' adoption of such systems. Methods This cross-sectional quantitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
(61 reference statements)
0
17
1
Order By: Relevance
“…Complaints concerning poor interoperability and integration between systems were found; these issues hindered both the implementation [48,61,93,98] and the adoption/use of EHRs and PHRs [44,47,51,56,134]. Clinicians' resistance [86,93,123,140] and lack of trust in EHRs/PHRs [66,92,98,114] regarding issues related to data privacy and the risk of data loss, which were key challenges to fully exploiting EHRs [43], were suggested. This was highlighted in a study which showed that the survey respondents (clinicians and staff) perceived a lack of trust in the reliability of EHRs and a lack of belief in their value for patient care to be barriers to EHR implementation (mean score 3.47 out of 5 and 4.46 out of 5) [58].…”
Section: Ehr/phr Systemmentioning
confidence: 99%
“…Complaints concerning poor interoperability and integration between systems were found; these issues hindered both the implementation [48,61,93,98] and the adoption/use of EHRs and PHRs [44,47,51,56,134]. Clinicians' resistance [86,93,123,140] and lack of trust in EHRs/PHRs [66,92,98,114] regarding issues related to data privacy and the risk of data loss, which were key challenges to fully exploiting EHRs [43], were suggested. This was highlighted in a study which showed that the survey respondents (clinicians and staff) perceived a lack of trust in the reliability of EHRs and a lack of belief in their value for patient care to be barriers to EHR implementation (mean score 3.47 out of 5 and 4.46 out of 5) [58].…”
Section: Ehr/phr Systemmentioning
confidence: 99%
“…Based on the World Health Organization's (WHO) recommendations, many countries have endeavored to implement e-health in their healthcare systems to improve healthcare deliveries (Al-Rayes et al, 2019). The impacts of e-health have been found with mixed results in different countries where e-health has been implemented.…”
Section: Review Of Literature On E-health In Saudi Arabiamentioning
confidence: 99%
“…The results revealed that users and non-users of the EHR system vary substantially on many factors such as perceived utility, perceived ease of use, social impact, and resistance to change. In addition, age, work experience, and medical specialties are strongly linked to the use of the EHR system by physicians (Al-Rayes et al, 2019). Concerning health care consumers, Alsahafi et al (2020) conducted a study to assess e-health literacy.…”
Section: Important Topics Covered By the Previous Work About Saudi Amentioning
confidence: 99%
“…Using the theoretical Technology Acceptance Model, they found that to increase the EHR systems' adoption rate, the design, social influence, and perception of the system's benefits need to be improved. 1 The authors' efforts should be commended in their systematic approach to improve EHR adoption for their institution and throughout their region.…”
mentioning
confidence: 99%
“…Some of the known challenges stem from issues that Al-Rayes et al faced in their present study. 1 In addition, interoperability, usability, technical limitations, and patient acceptance also impact the facilitation of EHR adoption. 12 Identifying these barriers early on may assist in successful implementation by allowing healthcare systems to anticipate and avoid these common barriers.…”
mentioning
confidence: 99%